Analisa Eksperimental Pengujian Turbin Angin Propeller Tiga Sudu Horizontal Axis - Islahuddin - Islahuddin; Sanny Ardhy; Meiki Eru Putra (Department of Mechanical Engineering, Universitas Andalas, 2021)
Energy needs in Indonesia are increasing every year along with the increase of human population. On the other hand, the rate of energy demand in Indonesia is not matched by the current energy availability. The lack of energy availability in Indonesia, one of which can be overcome by the use of alternative energy from nature, for example wind energy. Therefore, a three-blade horizontal axis propeller wind turbine was designed to obtain electrical energy. The design of this turbine uses several stages consisting of designing, assembling and testing the turbine. The test was conducted to determine the characteristics and performance of the wind turbine. Based on the initial design, the turbine sweep area is 2.4 m with three blades. The blade type is based on the NACA 2410 airfoil made of fiber composite and epoxy resin which is very effective at low wind speeds. The test was carried out on January 13-15, 2021 at Dharma Andalas University Padang with 16 hours for three days. Data recording is done with an automatic system using an octocoupler sensor, anemometer, and a voltage sensor integrated with a raspberry pi 3 microcontroller. From the tests carried out, the wind turbine starts to rotate at a Vcut-in of 1.5 m/s. The maximum rotation of the rotor obtained is 65 rpm with the highest wind speed of 3.9 m/s. The average power and average efficiency of the wind turbine are 9.8 Watt DC and 25.47%. The total electrical energy generated for 3 x 16 hours is 0.219 kWh.